Using Push-Pull-Legs Training : A Weight Training Method for Muscle Hypertrophy in Upper Body on Amateur Athletes - Geanta, Vlad Adrian (Arena-Journal of Physical Activities, 2022)
Introduction: Over time the information in the science of sports training is updated fantastically quickly. In weight training, in addition to classic training methods, the popularization of new training methods is sought, which come in support of the performer athlete or the individual who practices in the form of agreement, in achieving the stability objectives. The aim of this paper represent the hypertrophic effects that push-pull (PP) training can have on the upper body of amateur lifters. Methods: The study lasted for 6 weeks in a fitness center and the subjects (N = 6, M(y)23±1.1y, M(h)179.8±2.9 cm, M(w)74.3±2.9 kg, BMI(i)23.4±0.9kg/m2) were selected as participants. The routine consisted of 3 workouts/week. The participants trained using the method (PPL) but with the observation that the study followed the hypertrophic effects achieved on the upper body following the push-pull (PP) training. Measurements of the circumference of the pectoral (Ch), flexed arm (Ar) and the width of the shoulders (Sh), were measured using a metric band in two stages, an initial stage (Ch (i) 102±1.8, Ar(i) 37.8±0.8, Sh(i) 46.7±2.7, and a final, to see if it exists there is -500, and for height a tachometer. For evaluating body mass W(i), W (f) and body mass index BMI(i) BMI(f), we used an Omron HGF-500 scale, and a stadiometer for height. Results: After the 6 weeks of training, the expected hypertrophic results were recorded (BMI(f)22.2±0.7, W(f) 74.7±1.5, Ch (f)102.9±1.7, Ar(f)38.4±0.6, Sh(f)47.4±2.5). Alternatively, we used the T test (T = 2.01 for p <0.05) to tell us if there were any significant changes. We can say that the PP method is effective at the level of the upper train. Conclusions: Within the limits of the study, it can be concluded that significant changes can occur using the PP training method.